Selective polymerization catalysis: controlling the metal chain end group to prepare block copolyesters - Zhu,Y; Romain,C; Williams,CK (Journal of the American Chemical Society, 2015)
Selective catalysis is used to prepare block copolyesters by combining ring-opening polymerization of lactones and ring-opening copolymerization of epoxides/anhydrides. By using a dizinc complex with mixtures of up to three different monomers and controlling the chemistry of the Zn–O(polymer chain) it is possible to select for a particular polymerization route and thereby control the composition of block copolyesters.